An evaluation of the epidemiology of medication discrepancies and clinical significance of medicines reconciliation in children admitted to hospital. Issue 1 (13th November 2015) - Huynh, Chi; Tomlin, Stephen; Jani, Yogini; Solanki, Guirish A; Haley, Helen; Smith, Rachel E; Lowey, Andrew; Sinclair, Anthony; Wilson, Keith A; Wong, Ian Chi Kei; Terry, David
Abstract : Aims: To determine the incidence of unintended medication discrepancies in paediatric patients at the time of hospital admission; evaluate the process of medicines reconciliation; assess the benefit of medicines reconciliation in preventing clinical harm. Method: A 5 month prospective multisite study. Pharmacists at four English hospitals conducted admission medicines reconciliation in children using a standardised data collection form. A discrepancy was defined as a difference between the patient's preadmission medication (PAM), compared with the initial admission medication orders written by the hospital doctor. The discrepancies were classified into intentional and unintentional discrepancies. The unintentional discrepancies were assessed for potential clinical harm by a team of healthcare professionals, which included doctors, pharmacists and nurses. Results: Medicines reconciliation was conducted in 244 children admitted to hospital. 45% (109/244) of the children had at least one unintentional medication discrepancy between the PAM and admission medication order. The overall results indicated that 32% (78/244) of patients had at least one clinically significant unintentional medication discrepancy with potential to cause moderate 20% (50/244) or severe 11% (28/244) harm. No single source of information provided all the relevant details of a patient's medication history. Parents/carers provided the most accurate details of a patient's medication history in 81% of cases. Conclusions: This study demonstrates that in the absence of medicines reconciliation, children admitted to hospitals across England are at risk of harm from unintended medication discrepancies at the transition of care from the community to hospital. No single source of information provided a reliable medication history.